Utilization of Nickel Slag as an Aggregate Substitute in Asphalt Pavement Mixtures (AC-BC) - Bethary, Rindu Twidi; Intari, Dwi Esti; Mutaqin, Agung Huda (Jurnal Fondasi, 2023)
Developments in road construction and repair are currently increasing in number. The length of roads in Indonesia in 2020 according to the level of authority is 548,366 km (Ministry of Public Works and Public Housing; Prov / City Government Public Works Office). To support the smooth running of daily community activities, roads can connect one region to another. This study aims to determine how the effect of using nickel slag as a substitute for aggregate with nickel slag levels of 0%, 10%, 40% and 70% on the characteristics of the intermediate layer (AC-BC) by testing material and marshall characteristics. The results obtained from this study indicate that the use of nickel slag as an aggregate substitute meets the specifications of LFA class A. Through the marshall test referring to the 2018 bina marga general specifications, the ideal proportion of nickel slag addition to asphalt concrete mixtures is obtained based on the highest stability value in each mixture proportion that meets all the characteristics of the marshall mixture according to the 2018 bina marga general specifications Division 6 for the type of mixture of Asphalt Concrete Layer (Laston) Layer Between (AC-BC), namely at 70% slag contentwith 5.5% asphalt content with a stability value of 1098.30 kg. Where from the results of this study it can be concluded that the use of nickel slag as a substitute for aggregate can be utilized as a road pavement material because it meets the Bina Marga Standard Specifications.